COVID-19: What's Next? - Alfredo Ponce-; María Dolores Niembro-Ortega; María F. González-Lara (Permanyer, 2021)
Since December 2019, when severe acute respiratory syndrome coronavirus 2 emerged in Wuhan, China, this virus and the resulting disease, coronavirus disease (COVID-19), has spread worldwide. What has occurred in this year and a half goes beyond anything we have dealt with, as humankind, in the past two centuries, perhaps obscured only by war. An incredible number of articles, whether scientific or in the press, have been published, making it impossible to discern between what is biological and what is social in nature. Here, we aim to reflect on the basic structure of the virus and associate its behavior to that of determining factors of the human condition that may be modifiable soon. Needless to say, we find our effort clearly incomplete, and that both scientific and social aspects regarding COVID-19 or any other pandemic encountered in the future, will be constantly changing, from their beginning to their end.